Chronic kidney disease and dialysis therapy: incidence and prevalence in the world - Anna Filipska; Borys Bohdan; Piotr Paweł Wieczorek; Nataliia Hudz (Pensoft Publishers, 2021)
Сhronic kidney disease (CKD) is the important public and medical problem in the world because of a large burden on health care systems. The prevalence of CKD and number of dialysis patients are increasing in the world. The prevalence and incidence of CKD depends on age, race, and gender of patients, region, and the presence of the CKD registry in a country. Diabetes mellitus (DM) and arterial hypertension (AH) are the most common causes of end stage renal disease (ESRD). It is projected that the number of dialysis patients will reach 5.5 million in 2030. Specific strategies and interventions should be urgently aimed at reducing in the burden of CKD by means of the prevention, detection and treatment of DM, AH, and early stages of CKD. One more strategy is the organization of own domestic manufacture of solutions for dialysis therapy.